Design and optimization of the composition and mechanical properties for non-equiatomic CoCrNi medium-entropy alloys. (10th March 2023) - Yan, J.X.; Zhang, Z.J.; Zhang, P.; Liu, J.H.; Yu, H.; Hu, Q.M.; Yang, J.B.; Zhang, Z.F.
Highlights: The essential criterion was provided for the composition design of CoCrNi medium-entropy alloys (MEAs) with exceptional strength-ductility combinations. The analysis on phase stability, deformation mechanisms and mechanical properties is combined in the essential criterion. The optimal composition space of CoCrNi MEAs was predicted with the adoption of the essential criterion and first principles calculations. The validity of essential criterion was proved by systematic comparison with numerous experimental data. Abstract: The development of multi-principal element alloys (MPEAs, also called as high- or medium-entropy alloys, HEAs/MEAs) provides tremendous possibilities for materials innovation. However, designing MPEAs with desirable mechanical properties confronts great challenges due to their vast composition space. In this work, we provide an essential criterion to efficiently screen the CoCrNi MEAs with outstanding strength-ductility combinations. The negative Gibbs free energy difference ∆ E FCC-BCC between the face-centered cubic (FCC) and body-centered cubic (BCC) phases, the enhancement of shear modulus G and the decline of stacking fault energy (SFE) γ isf are combined as three requisites to improve the FCC phase stability, yield strength, deformation mechanisms, work-hardening ability and ductility in the criterion. The effects of chemical composition on ∆ E FCC-BCC, G and γ isf were investigated with the first principles calculations for Co x Cr33 Ni67- x, Co33 Cr y Ni67- y and Co z Cr66- z Ni34 (0 ≤ x, y ≤ 67 and 0 ≤ z ≤ 66) alloys. Based on the essential criterion and the calculation results, the composition space that displays the negative Gibbs free energy difference ∆ E FCC-BCC, highest shear modulus G and lowest SFE γ isf was screened with the target on the combination of high strength and excellent ductility. In this context, the optimal composition space of Co-Cr-Ni alloys was predicted as 60 at.%–67 at.% Co, 30 at.%–35 at.% Cr and 0 at.%–6 at.% Ni, which coincides well with the previous experimental evidence for Co55 Cr40 Ni5 alloys. The validity of essential criterion is further proved after systematic comparison with numerous experimental data, which demonstrates that the essential criterion can provide significant guidance for the quick exploitation of strong and ductile MEAs and promote the development and application of MPEAs.